A Reverse Suture Anchor Technique for Arthroscopic Medial Meniscus Root Repair - Chen-yang Meng, M.D.; Wei Feng, M.D.; Yi-zhong Ren, M.D.; Ming Liu, B.S.; Jun-yi Wang, B.S.; Chang-xu Han, M.D. (Arthroscopy Techniques, 2024)
Injuries of the posterior root of the medial meniscus can be accompanied by damage to the anterior cruciate ligament or often occur independently in cases of degenerative meniscal injury in older individuals. Anchor suture repair can achieve favorable biomechanical effects and clinical outcomes. However, anchor placement is technically challenging and requires a posterior medial approach, which increases the risk of iatrogenic injury. To address these issues, we have utilized the reverse anchor technique to repair the posterior root of the medial meniscus. This technique offers advantages such as reduced surgical time, simplified operation, and reduced risk of the “bungee effect” and iatrogenic injury.